Tapanuli Orangutan Feeding (Pongo tapanuliensis) In Sitandiang Hamlet, Bulu Mario Village, Sipirok District, South Tapanuli - Sinaga, Adinda Patricia Adelina; Setyawatiningsih, Sri Catur (Jurnal Biologi Tropis, 2025)
The tapanuli orangutan (Pongo tapanuliensis) is an endemic orangutan species found exclusively in the Batang Toru forest ecosystem, North Sumatra. Studying their natural diet is crucial to supporting conservation efforts for this critically endangered species. This research was conducted in Sitandiang Hamlet, Bulu Mario Village, Sipirok Sub-district, South Tapanuli Regency, with the aim of inventorying the types of food consumed by tapanuli orangutan and analyzing their feeding patterns in their natural habitat. The methods used included field surveys, interviews with local communities, and documentation. The findings revealed that tapanuli orangutan utilize a variety of plant resources, such as fruits, leaves, flowers, and tree bark. Their feeding patterns show a reliance on the availability of seasonal fruits, with an adaptation to consuming vegetative plant parts during off-fruit seasons. Local community knowledge about orangutan food sources also plays an important role in preserving their habitat. This study provides insights into ecosystem-based conservation management and emphasizes the importance of strengthening collaboration with local communities to support the sustainability of tapanuli orangutan populations in this region.